From the bottom left: The Azuayo Garden Path: Paciente Vázquez - Vásquez, Paciente (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
This study examines the Jardín Azuayo cooperative as an alternative to the capitalist model. Through a management approach rooted in the popular and solidarity-based economy, the organization prioritizes collective well-being and participatory democracy over profit. The research highlights the use of surplus funds for community development and cooperative education as tools for circumventing traditional power structures, thereby consolidating a financial system with a human-centered approach.